KOPSERINDO (KOPERASI SERAT RAMI INDONESIA) SEBUAH INDUSTRI PEMBERDAYAAN MASYARAKAT DESA (STUDI KASUS DI DESA PECEKELAN KECAMATAN SAPURAN KABUPATEN WONOSOBO) (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Local industry is very important to increase our society development, for excellent in rural society.Â Kopserindi is one of kind local industry about rami fber Those began form plant to produce becameÂ many form. Many kind produce is string, cotton, textile etc. Manufactured industry, certaintly neededÂ many of employer. The employer contain production employment and other employment.Keywords: Kopserindo, employment, local industry, society role